2023
DOI: 10.1093/rap/rkad042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on patients with rheumatoid arthritis: data from the Ontario Best Practices Research Initiative (OBRI)

Abstract: Objectives The COVID-19 pandemic created challenges for patients with rheumatoid arthritis (RA). We examined the potential impact of the pandemic on patient-reported outcomes (PROs), disease activity (DA), and medication profiles, comparing the periods pre-pandemic and during the pandemic. Methods Patients enrolled in the Ontario Best Practices Research Initiative were included if they had at least one visit with a physician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…Data from Canada indicate that disease activity in RA patients remained stable during the COVID -19 pandemic, with high persistence in bDMARD therapy and a significant increase in JAKi use. 49 In the present study, we have shown impaired adherence to intravenous a hospital -based, specialist -driven decisions. At the same time, regulations that would encourage the use of more affordable bDMARDs are limited, which leads to savings reallocation into enhanced access to other, higher -priced drugs.…”
Section: Discussionsupporting
confidence: 47%
“…Data from Canada indicate that disease activity in RA patients remained stable during the COVID -19 pandemic, with high persistence in bDMARD therapy and a significant increase in JAKi use. 49 In the present study, we have shown impaired adherence to intravenous a hospital -based, specialist -driven decisions. At the same time, regulations that would encourage the use of more affordable bDMARDs are limited, which leads to savings reallocation into enhanced access to other, higher -priced drugs.…”
Section: Discussionsupporting
confidence: 47%